Transcriptional Control of Mitosis: Deregulation and Cancer - Nath, Somsubhra; Ghatak, Dishari; Das, Pijush; Roychoudhury, Susanta (Frontiers in Endocrinology, 2015)
Research over the past few decades has well established the molecular functioning of mitosis. Deregulation of these functions has also been attributed to the generation of aneuploidy in different tumor types. Numerous studies have given insight into the regulation of mitosis by cell cycle specific proteins. Optimum abundance of these proteins is pivotal to timely execution of mitosis. Aberrant expressions of these mitotic proteins have been reported in different cancer types. Several post-transcriptional mechanisms and their interplay have subsequently been identified that control the level of mitotic proteins. However, to date, infrequent incidences of cancer-associated mutations have been reported for the genes expressing these proteins. Therefore, altered expression of these mitotic regulators in tumor samples can largely be attributed to transcriptional deregulation. This review discusses the biology of transcriptional control for mitosis and evaluates its role in the generation of aneuploidy and tumorigenesis.